2020
DOI: 10.1111/grs.12288
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating Pennisetum alopecuoides plants in a grazed pasture from unmanned aerial vehicles using object‐based image analysis and random forest classifier

Abstract: Timely and accurate weed detection in pasture is critical for efficient grazing management. Although high‐resolution images from unmanned aerial vehicles (UAVs) offer new opportunities for the detection of weeds at the farm scale, pixel‐based image analyses do not always produce the best results and object‐based image analysis (OBIA) has improved weed discrimination accuracy. In the present study, we evaluated the performance of OBIA on UAV images by integrating random forest (RF) classifier with auxiliary inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…In addition, the RF algorithm is receiving increased attention in remote sensing research as a highly suitable approach for high-resolution image data classification (Ma et al, 2015). By combining SLIC and RF, further classification improvements could be obtained (Csillik, 2017;Yasuda, 2018;Yuba et al, 2020b). We initially compared the performance of the SLIC-RF model using different input features of three color spaces (RGB, HSV and L*a*b*) and then combined these features with CHM, Texture and four VIs (ExG, ExR, GRVI, CIVE).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the RF algorithm is receiving increased attention in remote sensing research as a highly suitable approach for high-resolution image data classification (Ma et al, 2015). By combining SLIC and RF, further classification improvements could be obtained (Csillik, 2017;Yasuda, 2018;Yuba et al, 2020b). We initially compared the performance of the SLIC-RF model using different input features of three color spaces (RGB, HSV and L*a*b*) and then combined these features with CHM, Texture and four VIs (ExG, ExR, GRVI, CIVE).…”
Section: Discussionmentioning
confidence: 99%
“…García-Mateos et al (2015) compared 11 color spaces for classifying soil and plants in lettuce (Lactuca sativa) cultures using images from outdoor fields and found that the L*a*b* color space achieved the best performance with a* channels with 99.2% correct classification. Yuba et al (2020b) compared RGB and HSV color UAV images in discriminating Pennisetum alopecuoides plants in a pasture, and the results showed improved discrimination accuracy in the HSV-based SLIC-RF classifier. In the present study, by assessing the importance of input features (Figures 8 and 9), the HSV feature was considered the most important variable influencing the discrimination of crops, weeds and soils in the early growth stage of upland rice fields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The images from Canon S110 NIR (green, red, near-infrared) on UAV were also classified by Reis et al [42] by combining RF and maximum likelihood algorithms. Interestingly, Yuba et al [96] has tried to integrate OBIA and RF with auxiliary information layers in mapping P. alopecuroides, and they found that the combination of these algorithms has increased classification accuracy which is out of bag accuracy = 0.99 and generalized error accuracy i.e., 1.00 from the lowest altitude of 28 m.…”
Section: Algorithms and Classification Techniques For Weed Mappingmentioning
confidence: 99%
“…The few studies that explore this develop algorithms that run over the same region on the same data where image blurring techniques are applied to imitate the coarsening of spatial resolution [37][38][39]. Furthermore, attempts have been made to increase the relative altitude of the sensor to decrease the spatial resolution of the data [85]. Such methods do not effectively capture the relationship between feature's spatial resolution and the scale of measurement.…”
Section: Implications For Suitability For a Scale-standardised Object...mentioning
confidence: 99%